2002
DOI: 10.1034/j.1600-6143.2002.20409.x
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein C-III and E Polymorphisms and Cardiovascular Syndrome, Hyperlipidemia, and Insulin Resistance in Renal Transplantation

Abstract: Hyperlipidemia and insulin resistance frequently develop after renal transplantation, contributing to cardiovascular disease. Individual differences in response based upon genetic variations in proteins regulating lipidic and glucose tolerance metabolism could be expected. In the general population, the S2 allelic variant of the apoprotein (apo) C-III gene has been associated with hypertriglyceridemia and an insulin resistant state, whereas the E4 allele of the apo E has been associated with hypercholesterolem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Twenty-six studies [ 12 , 14 - 18 , 20 - 23 , 25 - 30 , 32 , 35 , 39 - 41 , 43 , 44 , 46 - 48 ], 10 studies [ 11 , 19 , 24 , 33 , 34 , 37 , 38 , 42 , 45 , 49 ] and 6 studies [ 13 , 31 , 36 , 50 - 52 ] involved Caucasians, Asians, and the subjects of other ethnic origins, respectively. Seven studies [ 12 , 16 , 21 , 22 , 30 , 35 , 50 ] only involved males, and the other 35 studies involved both males and females, among which 9 studies [ 14 , 23 , 26 , 28 , 29 , 36 , 37 , 43 , 47 ] separately provided data for males and females. Three studies [ 20 , 36 , 47 ] involved children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-six studies [ 12 , 14 - 18 , 20 - 23 , 25 - 30 , 32 , 35 , 39 - 41 , 43 , 44 , 46 - 48 ], 10 studies [ 11 , 19 , 24 , 33 , 34 , 37 , 38 , 42 , 45 , 49 ] and 6 studies [ 13 , 31 , 36 , 50 - 52 ] involved Caucasians, Asians, and the subjects of other ethnic origins, respectively. Seven studies [ 12 , 16 , 21 , 22 , 30 , 35 , 50 ] only involved males, and the other 35 studies involved both males and females, among which 9 studies [ 14 , 23 , 26 , 28 , 29 , 36 , 37 , 43 , 47 ] separately provided data for males and females. Three studies [ 20 , 36 , 47 ] involved children.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 18 , 33 , 38 , 48 ] and 9 studies [ 12 , 15 - 17 , 19 , 34 , 35 , 38 , 50 ] involved type 2 diabetes and CVD, respectively. Twenty-three studies [ 12 , 14 - 17 , 19 , 23 , 25 , 26 , 28 , 29 , 34 - 38 , 43 , 45 , 47 - 50 , 52 ] separately provided data for more than one subpopulation, and each subpopulation was treated as a separate comparison. Genotype distribution in 6 populations or subpopulations [ 25 , 27 , 31 , 38 , 50 , 51 ] significantly deviated -from HWE.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in agreement with many studies that have demonstrated that the S2 allele of ApoC-III/SstI polymorphism is associated with CHD in type 2 diabetes; [5][6][7] however, this association was not found by others. 23,24 The P2 allele has also been found to be associated with CAD by some 16,25 but not by others. 26,27 In our study, possession of the P2 allele does not appear to influence CHD risk in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the presence of apolipoprotein C‐III and E polymorphisms, genetic markers associated with insulin resistance and abnormal lipid profile in the general population respectively, have failed to show any significant correlation with these metabolic abnormalities in a posttransplantation setting (9). Although likely to be underpowered, this study highlights the difficulty of translating findings from the general population to solid‐organ transplant recipients.…”
Section: Concept and Putative Pathophysiologymentioning
confidence: 99%